Reasons for the Potential Implementation of Public-Private Partnerships in Ethiopian Road Infrastructure Provision - Yenenesh Ketema Gebre; Belachew Asteray Demsis (Advances in Civil Engineering)
Constructing and operating infrastructure facilities have traditionally been the responsibility of the public sector. Governments in several countries have been gradually enlisting the private sector in the provision of infrastructure through a public-private partnership. The purpose of this study is to investigate the reasons behind the potential implementation of public-private partnerships in Ethiopian road sector, which provide scientific support and rationales. There were both qualitative and quantitative research approaches used. A questionnaire survey was conducted, as well as an interview with industry professionals. To analyze the collected data, qualitative and quantitative data analyses were applied. The quantitative data were analyzed using version 26 of the Statistical Package for the Social Sciences software. The findings revealed scarcity in government funding, the inability of the public sector to assume all project risks, social strain on people due to poor road facilities, the demand for the skills and experience of the private sector, and the requirement for improvements in the levels of services as leading reasons for the potential implementation. The findings of the study provide scientific data and support for the adoption of public-private partnerships as they give solutions to the problems associated with road infrastructure delivery.